Sosialisasi Ekonomi Digital Dalam Upaya Peningkatan Pertumbuhan Kinerja UMKM di Desa Simodong - Yenni Mariani Sinurat; Suci Etri Jayanti; Daniel Collyn; Rapat Piter Sony Hutauruk; Fitrianingsih Fitrianingsih; Yomeini Sagala; Rika Surianto Zalukhu; Rodi Syafrizal; Ayu Zurlaini Damanik; Murbanto Sinaga (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The majority of MSME players in Simodong village have not optimized the use of digital technology in managing their business. Their understanding is also very limited regarding the digital economy and the benefits of technology in their business development. Therefore, community service activities in the form of socialization were held to MSME players in Simodong village, Sei Suka sub-district, Batu Bara district. This socialization activity aims to increase the understanding and knowledge of MSME actors about the digital economy. The socialization activity was attended by 20 participants. The methods used in this service activity are lectures and interactive discussions. The stages of service activities include the preparation stage, implementation stage and evaluation stage. After participating in the service activities, the understanding and knowledge of MSME actors about the digital economy increased. The majority of service activity participants have understood the concepts and benefits of the digital economy. Likewise, E-Commerce and online marketplaces and their benefits in increasing MSME sales have also been understood by the majority of participants. This activity has a significant impact in increasing the understanding and knowledge of participants.